Abnormal Hematological Indices in Cirrhosis - Amir A Qamar; Norman D Grace (Canadian Journal of Gastroenterology)
Abnormalities in hematological indices are frequently encountered in cirrhosis. Multiple causes contribute to the occurrence of hematological abnormalities. Recent studies suggest that the presence of hematological cytopenias is associated with a poor prognosis in cirrhosis. The present article reviews the pathogenesis, incidence, prevalence, clinical significance and treatment of abnormal hematological indices in cirrhosis.